The rough-face girl - Martin, Rafe, 1946-; Shannon, David, 1959- (New York : G.P. Putnam's Sons, 1992)
In this Algonquin Indian version of the Cinderella story, the Rough-Face Girl and her two beautiful but heartless sisters compete for the affections of the Invisible Being.
Keywords: Algonquin Indians -- Folklore; Cinderella (Tale); Indians of North America -- Folklore